Gambaran Kepatuhan Ibu Hamil dalam Mengonsumsi Tablet Fe Terhadap Kejadian Anemia di Wilayah Kerja Puskesmas Sadananya - Hapitri, Regina Eka; Fatimah, Siti (Journal of Midwifery and Public Health, 2022)
Anemia is a concerning condition for pregnant women. The World Health Organization (WHO) reports that the prevalence of anemia among pregnant women is around 35-37%, and this increases with the progression of pregnancy. Nutritional iron deficiency anemia tends to be more prevalent in developing countries than in developed ones. The incidence rate of anemia in Ciamis Regency, based on the health profile of the regency, is 20.05%. This study aims to depict the compliance of pregnant mothers in consuming iron (Fe) tablets concerning the occurrence of anemia in the working area of Sadananya Community Health Center in 2020. The research design employed in this study is descriptive research. The population consists of all pregnant mothers with anemia during pregnancy in the working area of Sadananya Community Health Center, Ciamis Regency, amounting to 723 individuals in the year 2020. Cluster Sampling technique was used for sample selection. The analysis conducted in this study is univariate. The research results revealed that almost all respondents, totaling 67 individuals (84.4%), were non-compliant in consuming Fe tablets, whereas a small portion of respondents, totaling 12 individuals (15.2%), exhibited compliance in consuming Fe tablets. In conclusion, the majority of respondents, 67 individuals (84.8%), were non-compliant in consuming Fe tablets. It is recommended that relevant institutions, particularly Sadananya Community Health Center, become more proactive in providing education to pregnant women about pregnancy-related anemia and the importance of consuming Fe tablets.